2007
DOI: 10.1128/jb.00976-07
|View full text |Cite
|
Sign up to set email alerts
|

The Extension of the Fourth Transmembrane Helix of the Sensor Kinase KdpD ofEscherichia coliIs Involved in Sensing

Abstract: The KdpD sensor kinase and the KdpE response regulator control expression of the kdpFABC operon coding for the KdpFABC high-affinity K ؉ transport system of Escherichia coli. In search of a distinct part of the input domain of KdpD which is solely responsible for K ؉ sensing, sequences of kdpD encoding the transmembrane region and adjacent N-terminal and C-terminal extensions were subjected to random mutagenesis. Nine KdpD derivatives were identified that had lost tight regulation of kdpFABC expression. They a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
0
20
0
3
Order By: Relevance
“…14 A putative K + -binding site is suspected within the cytoplasmic extension of transmembrane helix IV. 15,16 The effect of K + on KdpD activation was corroborated by the observation that transcription of kdpFABC is also induced when cells are grown in the presence of Cs + , a known inhibitor of K + uptake systems. 11 (iii) Studies with KdpD inserted in rightside-out membrane vesicles, in which the cytoplasmic domains are unidirectionally exposed to the lumen of the vesicles, indicated that an increase of the intraluminal ionic strength stimulates the kinase activity.…”
mentioning
confidence: 52%
“…14 A putative K + -binding site is suspected within the cytoplasmic extension of transmembrane helix IV. 15,16 The effect of K + on KdpD activation was corroborated by the observation that transcription of kdpFABC is also induced when cells are grown in the presence of Cs + , a known inhibitor of K + uptake systems. 11 (iii) Studies with KdpD inserted in rightside-out membrane vesicles, in which the cytoplasmic domains are unidirectionally exposed to the lumen of the vesicles, indicated that an increase of the intraluminal ionic strength stimulates the kinase activity.…”
mentioning
confidence: 52%
“…Interestingly, a cluster of positive and negative residues located at the water-lipid interface is also present in the tandempore K channel (TREK-1), the potassium sensor KdpD, the transient receptor potential proteins (TRPs), the OpuA transporter, and the mechanosensitive MscL channels ( Table 2). For some of them, it has been suggested that the charged residues could interact with the negative surface of the membrane, modulating activity (15)(16)(17)(18). We propose that highly charged residue clusters involved in signaling proteins and channels (Table 2) are able to adopt alternative states (unbound or bound to the membrane) in response to changes in mechanical properties of the lipid membrane, allowing this region to behave as a molecular switch for downstream protein activity.…”
Section: Discussionmentioning
confidence: 99%
“…Sugiura et al (37) suggested mechanistically different sensing mechanisms for potassium-limiting conditions and osmotic stress. However, Zimmann et al (44) showed that the extension of the fourth transmembrane helix encompassing the arginine cluster is mainly involved in sensing both stimuli, which may not be separable. Furthermore, Heermann et al (14) proposed an additional, more-complex regulatory network for kdpFABC expression.…”
mentioning
confidence: 99%